Efektivitas Loyalty Program dalam Customer Relationship Management terhadap Kepuasan dan Loyalitas Pelanggan (Studi Kegiatan Divisi Retensi dalam Pelaksanaan Loyalty Program Ã¢â‚¬Å“Im3@School CommunityÃ¢â‚¬Â pada PT Indosat Tbk. Kantor Cabang Malang) - Sari, Hesti Kartika (Jurnal ILMU KOMUNIKASI, 2009)
Abstract: The objective of this research is to analyze the influence of Loyalty Program in Customer Relationship Management (CRM) toward satisfaction and loyalty of PT Indosat Tbk. Malang Branch costumers. Loyalty Program is one of the customer retention’s strategies from PT Indosat Tbk. that belongs to development and application process of Customer Relationship Management (CRM). Dealing with that, a corporate could design a Loyalty Program that appropriate with their customers. This program will be very helpful for corporate to increase their customers’ satisfaction, and loyalty, and also to keep their customers influenced by others competitor’s offered. The data in this research analyzed by using linier regression analysis and the result of analysis shows that there are significant influence of Loyalty Program in Customer Relationship Management (CRM) toward costumer satisfaction and customer loyalty of PT Indosat Tbk. Malang Branch; and there are significant influence of satisfaction toward loyalty of PT Indosat Tbk. Malang Branch customers. Indeed, to produce loyal customer there is a need of strategy and has done by PT Indosat Tbk. through application of Customer Relationship Management with the highlight in Loyalty Program. This strategy proved could increase corporate business performs by increasing customer satisfaction and in the end could make the loyalty grow in them.